Ways to Increase the Effectiveness of Mechanisms for Regulating the Rural Labor Market - Ulug'murodova, N. B.; Rashidov, A. U. (International Journal of Human Computing Studies, 2022)
The article develops the concept of regulating the rural labor market, employment, increasing the competitiveness of the workforce, organizational improvement of employment services, achieving a balance between supply and demand for labor, a flexible labor market, employment of the rural population through human capital development.